Cobiotics a new conception of probiotics - Starovoitova, Svitlana (My University, 2019)
A new achievement in the study of probiotics was the formulation of a new concept - cobiotics. Cobiotics are more functional than synbiotics, since they are a combination of probiotics, prebiotics and digestive enzymes. This concept improves the nutritional value of synbiotics by incorporating various types of digestive enzymes and adding enzymes to isolate prebiotics from their natural sources. Cobiotics were first made in Belgium. The ingredients used in cobiotics create synergy that enhances their effectiveness and improves the effect of cofactors.
Keywords: кобіотики; пробіотики; мікробіота; кафедра біотехнології і мікробіології; кобиотики; пробиотики; микробиота; cobiotics; probiotics; microbiota